THE PROCEDURE FOR MEASUREMENT AND EVALUATION OF QUALITY OF PUBLIC TRANSPORT SERVICES - Konecny, Vladimir (Doprava a spoje, 2011)
The paper deals with measurement and evaluation of quality aspects of public transport services. Paper identifies the most important quality criteria in public transport. It includes the stages of proposal and application of quality measurement and evaluation system, too.